Banks vs. markets: Are banks more effective in facilitating sustainability? - David P. Newton; Steven Ongena; Ru Xie; Binru Zhao (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
Is bank- versus market-based financing different in its attitudes towards Environmental, Social, and Governance (ESG) risk? Using a novel sample covering 3,783 U.S. public firms from 2007 to 2020, we study how firm-level ESG risk affects its financing outcomes. We find that companies with higher ESG risk borrow less from banks than from markets, potentially to avoid bank monitoring and scrutiny. The Social and Governance components, in particular, matter. Furthermore, firms suffering higher numbers of negative ESG reputation shocks are less likely to continue to rely on bank credit in response to lenders' threats to end the lending arrangements. Finally, our results indicate that firms' ESG risk reduces after borrowing from banks but increases after bond issuance, suggesting that banks are more effective than public bond markets in shaping borrowers' ESG performance.
urn:nbn:fi:bof-202204271172
Keywords: G20; G21; G30; G32; 330; ESG risk; debt structure; capital structure; debt choices; bank monitoring